Balanced Scorecard Analysis On Private University Performance (Study At Economic Faculty Of Muhammadiyah Sorong University) - Evi Mufrihah Zain; Ahmad Jamil; Rosita Firda Sari; Febri Jein Andjar (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
Performance measurement is one way to assess the level of success or failure of public sector organizations in carrying out programs or policies that have been set in realizing the vision and mission. The obstacles faced by the Faculty of Economics in dealing with public trust and improving the accreditation of study programs require a method used to carry out performance measurement regularly and periodically. The Balanced Scorecard in the education sector can be adapted to meet various objectives in the education sector, such as determining the effect of BSC implementation on university research and innovation performance. The method used in this research is mix methods so that it can produce quantitative results on customer / student satisfaction and qualitative results on the operational activities of the Faculty of Economics. The results of this study indicate that faculty performance from a financial perspective is measured by the budget plan for the annual economic faculty work program and the realization of work programs carried out at the Faculty. Non-financial performance, the perspective of internal business is described by the achievement of the Faculty's vision and mission, the growth and learning perspective is described through the utilization of the Faculty's human resources and the customer perspective is measured through student satisfaction. Balanced Scorecard is able to measure university performance, especially in the faculty of economics.